NF-κBp50 and HDAC1 Interaction Is Implicated in the Host Tolerance to Infection Mediated by the Bacterial Quorum Sensing Signal 2-Aminoacetophenone - Bandyopadhaya, Arunava; Tsurumi, Amy; Rahme, Laurence G. (Frontiers in Microbiology, 2017)
Some bacterial quorum sensing (QS) small molecules are important mediators of inter-kingdom signaling and impact host immunity. The QS regulated small volatile molecule 2-aminoacetophenone (2-AA), which has been proposed as a biomarker of Pseudomonas aeruginosa colonization in chronically infected human tissues, is critically involved in “host tolerance training” that involves a distinct molecular mechanism of host chromatin regulation through histone deacetylase (HDAC)1. 2-AA’s epigenetic reprogramming action enables host tolerance to high bacterial burden and permits long-term presence of P. aeruginosa without compromising host survival. Here, to further elucidate the molecular mechanisms of 2-AA-mediated host tolerance/resilience (HT/R) we investigated the connection between histone acetylation status and NF-B signaling components that together coordinate 2-AA-mediated control of transcriptional activity. We found increased NF-Bp65 acetylation levels in 2-AA stimulated cells that are preceded by association of CBP/p300 and increased histone acetyl transferase (HAT) activity. In contrast, in 2-AA tolerized cells the protein-protein interaction between p65 and CBP/p300 is disrupted and conversely, the interaction between p50 and co-repressor HDAC1 is enhanced, leading to repression of the pro-inflammatory response. These results highlight how a bacterial QS signaling molecule can establish a link between intracellular signaling and epigenetic reprogramming of pro-inflammatory mediators that may contribute to host tolerance training. These new insights might contribute to the development of novel therapeutic interventions against bacterial infections.